2020
DOI: 10.1002/adfm.202001756
|View full text |Cite
|
Sign up to set email alerts
|

Laser Assisted Solution Synthesis of High Performance Graphene Supported Electrocatalysts

Abstract: Simple, yet versatile, methods to functionalize graphene flakes with metal (oxide) nanoparticles are in demand, particularly for the development of advanced catalysts. Herein, based on light-induced electrochemistry, we report a laser-assisted, continuous, solution route for the simultaneous reduction and modification of graphene oxide with catalytic nanoparticles. Electrochemical graphene oxide (EGO) was used as starting material and electron-hole pair source due to its low degree of oxidation, which imparts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Unlike other chemical and thermal reduction methods, laser reduction is characterized by energy absorption by the GO films dependent on the radiation wavelength and pulse width. From the wavelength perspective, the photoreduction of GO generally can be achieved photochemically with radiation wavelength in the UV region 36 and photothermally using radiation from visible to IR 37 . From the temporal perspective, the laser–matter interaction occurs in a clear time sequence 38 : excitation of an electron by incident photon occurs in the first ~100 fs, following by electron–phonon coupling from 100 fs to 10 ps, finally from 100 ps or longer heat dissipate to the surrounding matrix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other chemical and thermal reduction methods, laser reduction is characterized by energy absorption by the GO films dependent on the radiation wavelength and pulse width. From the wavelength perspective, the photoreduction of GO generally can be achieved photochemically with radiation wavelength in the UV region 36 and photothermally using radiation from visible to IR 37 . From the temporal perspective, the laser–matter interaction occurs in a clear time sequence 38 : excitation of an electron by incident photon occurs in the first ~100 fs, following by electron–phonon coupling from 100 fs to 10 ps, finally from 100 ps or longer heat dissipate to the surrounding matrix.…”
Section: Resultsmentioning
confidence: 99%
“…When the ps UV laser was applied, photochemical removal of functional groups was expected 42 . The photon energy of the 355 nm light is 3.49 eV can excite single-photon-mediated valence-to-conduction band transition of EGO (with a direct bandgap range from 3.25 to 3.95 eV) 36 , 43 . While for the 1064 nm beam at a photon energy of ~1.17 eV, multiphoton process is required to excite EGO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the 1064 nm laser mainly induced vibration of water molecules, then the stretched OH groups of water molecules facilitated the hydrolysis reaction of metal ions and led to the formation of ([Ni 0.15 Mn 0.15 Co 0.7 (OH) 2 ](NO 3 ) 0.2 ·H 2 O) hydroxide nanostructures. Recently, Liu et al [ 135 ] reported a laser-assisted, continuous, solution route for the simultaneous reduction and modification of graphene oxide with Pt, PtPd alloys, RuO 2 and MnO x nanoparticles, which demonstrated the versatility of PLICN in synthesizing functional nanoparticle-modified graphene materials.…”
Section: Laser As the Synthetic Techniquementioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) is mainly used to study the elements on the surface of materials and their different valence states. Peng et al [41] synthesized high-performance graphenesupported electrocatalysts by laser-assisted solution. The valence state characterization of Ru by XPS showed that Ru mainly existed in the Ru 4+ state, while Pt mainly existed in the Pt 0 form, and a small part was Pt 2+ .…”
Section: Characterization Of Graphene-based Nanocompositesmentioning
confidence: 99%